2014
DOI: 10.4103/1995-705x.151084
|View full text |Cite
|
Sign up to set email alerts
|

Tight glycemic control and cardiovascular effects in type 2 diabetic patients

Abstract: Diabetes Mellitus (DM) with poor glycemic control is one of the leading causes for cardiovascular mortality in diabetic patients. Tight glycemic control with glycosylated haemoglobin of <7 gms% is recommended as a routine and < 6.5 gms% is recommended for young and newly diagnosed diabetics. Treatment goal aims at achieving near normal blood glucose level, and directed at management of other co morbid conditions such as obesity, hypertension and dyslipidemia. Oral hypoglycemic agents are the preferred drugs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 62 publications
0
16
0
2
Order By: Relevance
“…Also, the classification of type II DM based on tongue thermogram using deep learning methods was not initiated till today. e poor glycaemic control in diabetic subjects leads to the cardiovascular problems; therefore tight glycaemic control (HbA 1c of <7%) recommended for the prevention of the onset of disease was discussed by Moodahadu et al [56]. of good glucose control, the endothelial cell levels were found to be higher in the diabetic subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the classification of type II DM based on tongue thermogram using deep learning methods was not initiated till today. e poor glycaemic control in diabetic subjects leads to the cardiovascular problems; therefore tight glycaemic control (HbA 1c of <7%) recommended for the prevention of the onset of disease was discussed by Moodahadu et al [56]. of good glucose control, the endothelial cell levels were found to be higher in the diabetic subjects.…”
Section: Resultsmentioning
confidence: 99%
“…It has not yet been conclusively determined as to which target level of HbA1c, i.e., HbA1c <6.5% or HbA1c <7.0%, might be the more appropriate target level representing good glycemic control [25]. In the present study, when the patients were further subclassified according to the glycemic control status into an intensive glycemic control group (HbA1c <6.5%) and a non-intensive, but good glycemic control group (HbA1c 6.5–7.0%), no significant difference of the changes of the baPWV during the study period was observed between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, when the patients were further subclassified according to the glycemic control status into an intensive glycemic control group (HbA1c <6.5%) and a non-intensive, but good glycemic control group (HbA1c 6.5–7.0%), no significant difference of the changes of the baPWV during the study period was observed between the two groups. While intensive glycemic control is thought to be beneficial against inflammation, oxidative stress, and/or accumulation of AGEs, transient hypoglycemia associated with intensive control might activate the sympathetic tone [5, 25]; thus, intensive glycemic control may have some counteractive effects on the arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes Mellitus (DM) with poor glycemic control is one of the leading causes for cardiovascular mortality in diabetic patients. [18] Metformin: It is a first-line therapy for patients with type 2 diabetes but contraindicated in individuals with severe heart failure (HF) classes III-IV [as per New York Heart Association, NYHA] due to lactic acidosis associated mortality rate of 50%. [3] Sulfonylureas (SU): Acute hypoglycaemia induced by sulfonylureas, may trigger ischemia and cardiovascular events.…”
Section: Cardiovascular Impact Of Oral Hypoglycemic Agentsmentioning
confidence: 99%